Comercio exterior y crecimiento económico, revisión de la teoría y la evidencia empírica. (2021)
In this paper a revision of the theory about the relation among foreign trade of manufactured products and economical growth is done, therefore it is emphasized in the predominant perspective of the recent literature that suggests that the growth of the manufacturing exports generates increasing revenues in the related sectors , according to the called « Law of Verdoorn « and to external factors in the nonexportable sectors. In a complementary way the empiric accumulated evidence is explored, giving special attention to the Colombian case and some results of new exercises for the national and regional contours are given.